A Literature Review : Riset Intellectual Capital di Indonesia - Sari, Imelia; Azmi, Zul; Nadella, Suraya; Diny, Nola Rahma; Harefa, Cahayu Prildana (CV. ITTC INDONESIA, 2025)
This study aims to analyze trends and developments in research on Intellectual Capital (IC) in Indonesia during the 2020–2024 period using a Systematic Literature Review (SLR) approach. Thirty-five articles from SINTA and Scopus-accredited journals were used as the unit of analysis, classified by main topic, industry sector, methodological approach, and number of citations. The results show that the most frequently studied topic is the influence of IC on firm value, followed by IC coverage (ICD) and financial performance. Most studies use a quantitative approach with secondary data, while qualitative and multidimensional approaches are still very limited. The manufacturing sector dominates the research objects, with low representation of other knowledge-intensive sectors. Furthermore, the use of strategic management theories such as the Resource-Based View (RBV) and Knowledge-Based View (KBV) is not optimal. This study contributes to describing the direction and outlook of IC research in Indonesia and recommends the need for a more exploratory, cross-sectoral, and theoretically sound approach for the development of future IC studies.